Mesoscale Convective Complex Verification on Heavy Rain in Semarang (Case Study: 13 March 2024) - Didik Kurniawan; Binsar Hakim Aritonang; Helena Yaku; Imma Redha Nugraheni (BULETIN FISIKA, 2025)
This study aims to identify the Mesoscale Convective Complex (MCC) pattern during a heavy rain event in Semarang City on March 13, 2024, using Himawari-9 satellite imagery. The analysis was based on Maddox's (1980) criteria, including cloud coverage, duration, and convective system eccentricity. The results show that MCC met the requirements with a 7-hour duration, a maximum eccentricity of 0.9498, and shield and core areas of 108,228 km² and 89,128 km², respectively. MCC produced moderate to extreme rainfall intensities, peaking at 60–70 mm/h. MCC activity began in Semarang and moved southwestward, posing hydro-meteorological disaster risks such as flash floods. This study emphasizes the importance of MCC monitoring for hydro-meteorological disaster mitigation in Indonesia.